The Relationship between Type 2 Diabetes Mellitus with Chronic Kidney Disease In Indonesian Population In 2014-2015 (Data Analysis of IFLS 5) - Simanjuntak, Tri Damayanti; Wahyono, Tri Yunis Miko (UI Scholars Hub, 2020)
The Global Burden of Disease research in 2010 reveal that cases of chronic kidney disease increase and became a serious health problem. Indonesia Basic Health Research data in 2013 reveal that the proportion of patients with chronic kidney failure aged > 15 years old based on doctor’s diagnosis was 0,2% and 0,6% kidney stones. The study aimed to analyze the relationship be tween type 2 diabetes mellitus and chronic kidney disease in the population of Indonesia in 2014-2015. This design of research used cross-sectional and secondary data from the Indonesia Family Life Survey (IFLS) 5. The minimum sample size in this study was 792 people with technique used total sampling, which found 34,012 people who meet the inclusion and exclusion criteria. The prevalence of chronic kidney disease in Indonesia population in 2014 – 2015 was 1%. The result of chi-square test of the rela tionship between type 2 diabetes mellitus and chronic kidney disease in the Indonesian population showed POR=2.48 (95%CI 1.422-4.071; p-value =0.0002). Multivariate analysis with logis tic regression tests POR 1.88 (95% CI 1.124 - 3.168; p-value = 0.016) after smoking status and history of high cholesterol were controlled. Patients with type 2 diabetes mellitus expects to make appropriate treatment efforts to prevent complications of chronic kidney disease.